(untitled) (Journal of Nuclear Technology in Applied Science, 2025)
The present paper explores the quantum simulation of cold fusion phenomena using superfluid helium. Leveraging the unique properties of superfluid helium, such as ultracold temperatures and stability, an approach has been taken to simu late D-D nuclear fusion relevant to cold fusion scenarios with Quantum Monte Carlo Methods and Density Functional Theory.Furthermore the present study investigates quantum degeneracy effects, including Bose-Einstein condensation and superfluidity that influence reaction dynamics and product distributions. Based on computational simulations and theoretical analysis the interplay be tween nuclear dynamics and quantum phenomena in cold fusion has been eluci dated.The present study proposes a promising approach to unlock the mysteries of cold fusion research and realizing practical fusion energy applications.